THE HUMAN DIMENSION IN INTELLIGENT LIVING ENVIRONMENT - Masi Muhammadi (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2011)
Due to the rapid aging of the Dutch population and aging-in-place policies, anincreasing demand for suitable dwellings focused on the human dimension of construction is to be expected. This global issue of aging in place is a wakeup call for us architects to move towards constructions that empower this active aging. A significant contribution can be provided by “Domotics”; which is defined as the advanced technological equipments and services in the domestic environment to sustain and to enhance the quality of aging in place as well as empowerment of the senior citizen (in daily life). This paper is based on literature review, qualitative and quantitative studies i) it seeks to inform the development of domotics technology in the living environment of the older adults; ii) it provides an overview of the multiplicity of needs and attitudes of the older citizens in regards to smart technology in the domestic environment; iii) and develops recommendations to incorporate domotics in the architectural structure of the dwelling keeping the Human factor in mind. This study on senior citizens’ needs and attitudes toward domotics is based upon a triangulation of cohort-group discussions, enabling techniques and in-depth interviews followed by a postal questionnaire survey. The findings indicate that needs, perceptions, environmental and personal attributes of the seniors determine their attitudes towards automation. This attitude can be described as ‘critical/positive’. Too much automation, where little or no consideration is put towards the user’s needs, is regarded as undesirable. Ethical considerations are particularly related to, professional stakeholders, especially caregivers, whereas seniors are mainly interested in the functionality of domotics. The integration and domestication of domotics in a house needs to be a synthesis of the user’s needs, technology, the living environment, services and healthcare.To enable aging in place and the acceptance of (care through) domotics we need, i) to familiarize inhabitants with smart technology, ii) to domesticate and personalize it, iii) as well as to (imperceptibly) apply need-based technology in the (pre-existing) homes.